Reflexões sobre homofobia e educação em escolas do interior paulista - Teixeira-filho, Fernando Silva [UNESP]; Rondini, Carina Alexandra [UNESP]; Bessa, Juliana Cristina [UNESP] (Faculdade de Educação da Universidade de São Paulo, 2011)
This is a survey conducted in 2009 with 2,282 students of both sexes enrolled in the three grades of high school in three cities of the west of Sao Paulo state (Assis, Presidente Prudente and Ourinhos). The data collection instrument was a self-administered and anonymous questionnaire with 131 questions. In this article, we reflect on how in schools the research participants reproduce and reinforce the hegemonic discourses of control of sexualities guided by the attempt to promote heterosexuality as the only form of sexual intelligibility, to the detriment of other forms of expression of sexuality. We discuss how homophobia and the devices of social control of sexuality (re) produce prejudices and stereotypies, resulting in vulnerabilities that non-heterosexual teenagers have, such as homophobic victimization, social and affective isolation, ideations and suicide attempts. The study shows that the invariant were discrimination, homophobic violence and the insults that are perpetrated in the values and discourses of adolescents at school and in their family, demonstrating the institutionalization of homophobia as a regulatory practice of the psychological and social construction of gender and sexual identities. We highlight how important it is for the school to appropriate the means of deconstruction of heterocentric normativity to preserve the rights and citizenship of the people who do not identify with the prevailing models of heterosexuality.

Trata-se de um estudo do tipo survey realizado em 2009 junto a 2.282 estudantes de ambos os sexos cursando as três séries do ensino médio em três cidades do interior do Oeste Paulista (Assis, Presidente Prudente e Ourinhos). O instrumento de coleta de dados foi um questionário autoaplicável e anônimo com 131 questões. Neste artigo, reflete-se sobre o quanto @s participantes da pesquisa reproduzem e reforçam, no espaço escolar, os discursos hegemônicos de controle das sexualidades pautados na tentativa de fazer prevalecer a heterossexualidade como a única forma de inteligibilidade sexual, em detrimento de outras formas de manifestação da sexualidade. Discute-se como a homofobia e os dispositivos de controle social das sexualidades (re)produzem preconceitos e estereotipias, resultantes em vulnerabilidades que os adolescentes não-heterossexuais apresentam, tais como: vitimização homofóbica, isolamentos sociais e afetivos, e ideações e tentativas de suicídio. O estudo mostra que o invariante foram as discriminações, as violências homofóbicas e as injúrias que são perpetradas nos valores e discursos dos adolescentes em situação escolar e familiar, demonstrando a institucionalização da homofobia como prática regulatória da construção social e psicológica de gêneros e identidades sexuais. Destaca-se quão importante é, para a escola, apropriar-se de meios de desconstrução das normativas heterocentradas, visando preservar os direitos e a cidadania de pessoas que não se identificam aos modelos vigentes da heterossexualidade.
Reflections on homophobia and education in schools in the interior of Sao Paulo state
Keywords: Homophobia and education; Homophobic violence; Adolescence; Sexuality; Homosexuality; Homofobia e educação; Violência homofóbica; Adolescência; Sexualidade; Homossexualidade